Expression and Cellular Distribution of Glucose Transporters and Alpha Subunits of Na+/K+-ATPase in the Heart of Fructose-fed Female Rats: The Role of Estradiol - Koricanac, G.; Tepavcevic, S.; Romic, S.; Milosavljevic, T.; Stojiljkovic, M.; Zakula, Z. (Hormone and Metabolic Research, 2014)
Remarkable parallels are observed between glucose transporters (GLUT) and subunits of Na+/K+-ATPase, which deal with insulin regulation, tissue specificity, intracellular distribution and function of these proteins. To test our hypothesis that similarities also exist in alteration of cardiac GLUTs and alpha subunit isoforms of the pump in insulin resistance, animal model of fructose rich diet was exploited. The role of estradiol in regulation of GLUTs and Na+/K+-ATPase in insulin resistance context was studied as well. Cardiac protein expression, as well as insulin-regulated cellular localization of GLUT4, GLUT1, and α1 and α2 subunits of the pump were analyzed by Western blot. Fructose rich diet increased plasma insulin level and HOMA index, while estradiol treatment reversed both parameters to the control level. We did not observe obvious similarities in the pattern of alterations of GLUT1/α1 subunit of the pump, as well as GLUT4/α2 subunit, related to diet or hormone treatment. Considering alterations in expression and cellular localization of GLUTs and the pump subunits, fructose rich diet jeopardized cardiac glucose transport in some extent, but in contrast, stimulated Na+/K+-ATPase function. Estradiol treatment opposed the fructose diet biochemical action and the effect on cardiac GLUTs, but was inefficient concerning the changes of cardiac Na+/K+-ATPase subunits. Changes of the cardiac molecules can be mediated by alterations in the level of insulin and nonesterified fatty acids, induced by the diet and hormone treatment.
Keywords: fructose; estradiol; glucose transporter; sodium-potassium-exchanging ATPase; heart